PSYCHOEDUCATION OF ASSERTIVE COMMUNICATION TO IMPROVE BULLYING PREVENTION KNOWLEDGE IN JUNIOR HIGH SCHOOL STUDENTS - Nanda, Kharisma; Rachmawati, Henny; Mahmudah, Siti; Fadillah, Elmiah; Maryam, Effy Wardati; Widyastuti, Widyastuti (Antis-publisher, 2025)
Objective: This psychoeducational activity aims to increase understanding related to bullying and assertive communication in SMPN 1 Purwosari students. Method: The method used in this psychoeducational activity uses the lecture method by psychologists, accompanied by pre-post-test evaluation, to measure participants' understanding. Results: The data analysis technique used the T test paired sample T-test, with a result of 0.001, meaning that there was a significant difference in participants' understanding before and after psychoeducation. Novelty: The psychoeducational approach and the use of paired sample T-test for measuring understanding before and after the activity may contribute to the novelty.